Content based video retrieval using discrete cosine transform - Sumaya Hamad; Ahmeed Suliman Farhan; Doaa Yaseen Khudhur (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
A content based video retrieval (CBVR)framework is built in this paper.  One of the essential features of video retrieval process and CBVR is a color value. The discrete cosine transform (DCT) is used to extract a query video features to compare with the video features stored in our database. Average result of 0.6475 was obtained by using the DCT after implementing it to the database we created and collected, and on all categories. This technique was applied on our database of video, Check 100 database videos, 5 videos in each category.